USE OF INNOVATIVE TECHNOLOGIES IN PROFESSIONAL TRAINING OF HIGHER EDUCATION ACQUIRES OF PHYSICAL EDUCATION AND SPORTS (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the importance of using information technologies in the professional training of future specialists in physical education and sports. Taking into account the research of a number of scientists, it was established that the issues of transformation in the field of physical culture and sports remain relevant in the conditions of globalization and the modern information space. It was determined that the introduction of innovations in educational, educational and training processes in various types of sports, health and recreational movement activities of various population groups is one of the main factors in the formation of the creative informational potential of future specialists in the field of physical culture and sports. Theoretical and methodological substantiation of the implementation of the concept of management of the educational and training, physical culture and health-improving process using the innovative method of the express test for assessing the physical state of the physiological systems of the body of athletes of various specializations and qualifications, people of different ages, articles and the functional readiness of their bodies for the use of information-computer computer technologies is given. The practical implementation of this approach is the use of modern achievements of ICT technologies.It is shown that the use of a computer program in the field of physical education and sports allows to quickly quantitatively assess the parameters of the cardiovascular and respiratory systems, structural components and the integral level of functional fitness of the body, to reveal the dynamics of the level of physical fitness, i.e. to carry out comprehensive control of changes in the physical state of the body and provide an assessment of the effectiveness of the use of training tools.It has been proven that the use of information technologies provides an opportunity to obtain information on the specifics of changes in the main indicators of physical and functional fitness in the process of adaptation to systematic physical loads of different orientation, volume and intensity, and for students of higher education in physical culture and sports to form an appropriate knowledge system of the information and educational space for future professional activities.
Keywords: information and computer technologies; competences; professional training; computer program; students of higher education